Translanguaging: Implications for the language classroom derived from the revised version of the CEFR - Lankiewicz, Hadrian Aleksander (Glottodidactica, 2021)
One of the basic documents defining, among others, language learning, teaching, and assessment within the EU is the CEFR (2001). Since the moment of its first publication, many political and social changes have occurred which necessitated the reshaping of general language teaching policy to meet the new conditions. There also appeared new theoretical reflections on the process of language learning and language use. Through enhanced mobility a remarkable number of European citizens have become plurilingual, living in multilingual environments. On the other hand, new insights into the process of language learning and teaching accentuated the need for the departure from monolingual approaches in favour of translingual practices (Canagarajah 2013; García & Li 2014). The objective of this article is to present the implications derived from a translingual instinct (Li 2011) for teaching an additional foreign language to plurilingual students. The author of the article derives his reflections from the theoretical underpinnings of multilingualism, his own research on translanguaging and the revised version of the CEFR (2018).